Influence of shared and innovative mobility on psychological wellbeing - Rosa Arroyo López; Tomás Ruiz Sánchez; Lidón Mars Aicart (Renewable Energy and Sustainable Development)
Recently, new travel options such as micromobility and shared transport systems have been introduced in many urban areas in Spain, which are intended to increase the sustainability and accessibility of cities. The Covid-19 pandemic has boost the use of these new individual travel modes. In this conference paper, travel behavior and wellbeing of users of this new urban solutions compared to traditional transport modes are analyzed. Face-to-face and online surveys were carried out during the Summer of 2021 in Valencia (Spain) to collect information regarding travel behavior and wellbeing. Participants were habitual users of all urban travel modes, including those who also used motosharing, carsharing or private e-scooters. Satisfaction with Travel Scale (STS) is used to explore subjective wellbeing of users of new and traditional transport modes. Results show that current users of motosharing and private e-scooters were former users of public transport, while users of carsharing used to utilize more car and motosharing before. On the other hand, active transport is associated with higher satisfaction compared to new urban modes, while they provide more satisfaction than urban public transport.   Received: 16 November 2023 Accepted: 10 March 2024 Published: 27 March 2024